Actual status of patient information sharing among healthcare delivery facilities: a survey by the third subcommittee, committee on academic research, the Japanese society of hospital pharmacists - Daisuke Kikuchi; Masami Tsuchiya; Shiro Hatakeyama; Yuichi Tasaka; Takeshi Uchikura; Ryohkan Funakoshi; Taku Obara (BMC, 2022)
Abstract Background Information sharing among medical professionals is important for providing quality medical care. The purpose of the present study was to elucidate the actual status of information sharing between hospitals and other healthcare delivery facilities by surveying information sharing among the pharmaceutical departments of Japanese hospitals in 2020 conducted by the Japanese Society of Hospital Pharmacists. Methods Responses were received from 3612 (43.6%) of the 8278 target medical institutions between May 2020 and August 2020. Results The proportions of hospitals that shared information with community pharmacies, other hospitals, and long-term nursing homes were 40.6%, 36.4%, and 27.3%, respectively. While tracing reports were the most common tool used by hospitals for information sharing with community pharmacies (54.3%), drug summaries were used for sharing information with other hospitals and long-term nursing homes (77.4% and 78.0%, respectively). The proportion of hospitals sharing information with community pharmacies and other hospitals showed a tendency to increase as the number of hospital beds increased. No relationship could be established between the number of hospital beds and the proportion of hospitals sharing information with long-term nursing homes. Conclusion Information between hospitals and community pharmacies was shared primarily using tracing reports, whereas information between hospitals and other hospitals and long-term nursing homes was primarily shared via drug summaries.